Repurposing a PICU for Adult Care in a State Mandated COVID-19 Only Hospital: Outcome Comparison to the MICU Cohort to Determine Safety and Effectiveness - Gist, Ramon E.; Pinto, Rohit; Kissoon, Niranjan; Ahmed, Youssef E.; Daniel, Pia; Hamele, Mitchell (Frontiers in Pediatrics, 2021)
Objective: The ongoing coronavirus 2019 (COVID-19) pandemic is disproportionally impacting the adult population. This study describes the experiences after repurposing a PICU and its staff for adult critical care within a state mandated COVID-19 hospital and compares the outcomes to adult patients admitted to the institution’s MICU during the same period. Design: A retrospective chart review was performed to analyze outcomes for the adults admitted to the PICU and MICU during the 27-day period the PICU was incorporated into the institution’s adult critical care surge plan. Setting: Tertiary care state university hospital. Patients: Critically ill adult patients with proven or suspected COVID-19. Interventions: To select the most ideal adult patients for PICU admission a tiered approach that incorporated older patients with more comorbidities at each stage was implemented Measurements and Main Results: There were 140 patients admitted to the MICU and 9 patients admitted to the PICU during this period. The mean age of the adult patients admitted to the PICU was lower (49.1 vs. 63.2 p=0.017). There was no statistically significant difference in the number of comorbidities, intubation rates, days of ventilation, dialysis or LOS. Patients selected for PICU care did not have coronary artery disease, CHF, cerebrovascular disease or COPD. Mean admission Sequential Organ Failure Assessment (SOFA) score was lower in patients admitted to the PICU (4 vs 6.4, p = 0.017) with similar rates of survival to discharge (66.7% vs 44.4%, p= 0.64). Conclusion: Outcomes for the adult patients who received care in the PICU did not appear to be worse than those who were admitted to the MICU during this time. While limited by a small sample size, this single center cohort study revealed that careful assessment of critical illness considering age and type of co-morbidities may be a safe and effective approach in determining which critically ill adult patients with known or suspected COVID-19 are the most appropriate for PICU admission in general hospitals with primary management by its physicians and nurses.